Genomic Analysis Based on Chromosome-Level Genome Assembly Reveals an Expansion of Terpene Biosynthesis of Azadirachta indica - Du, Yuhui; Song, Wei; Yin, Zhiqiu; Wu, Shengbo; Liu, Jiaheng; Wang, Ning; Jin, Hua; Qiao, Jianjun; Huo, Yi-Xin (Frontiers in Plant Science, 2022)
Azadirachta indica (neem), an evergreen tree of the Meliaceae family, is a source of the potent biopesticide azadirachtin. The lack of a chromosome-level assembly impedes an in-depth understanding of its genome architecture and the comparative genomic analysis of A. indica. Here, a high-quality genome assembly of A. indica was constructed using a combination of data from Illumina, PacBio, and Hi-C technology, which is the first chromosome-scale genome assembly of A. indica. Based on the length of our assembly, the genome size of A. indica is estimated to be 281 Mb anchored to 14 chromosomes (contig N50 = 6 Mb and scaffold N50 = 19 Mb). The genome assembly contained 115 Mb repetitive elements and 25,767 protein-coding genes. Evolutional analysis revealed that A. indica didn’t experience any whole-genome duplication (WGD) event after the core eudicot γ event, but some genes and genome segment might likely experienced recent duplications. The secondary metabolite clusters, TPS genes, and CYP genes were also identified. Comparative genomic analysis revealed that most of the A. indica-specific TPS genes and CYP genes were located on the terpene-related clusters on chromosome 13. It is suggested that chromosome 13 may play an important role in the specific terpene biosynthesis of A. indica. The gene duplication events may be responsible for the terpene biosynthesis expansion in A. indica. The genomic dataset and genomic analysis created for A. indica will shed light on terpene biosynthesis in A. indica and facilitate comparative genomic research of the family Meliaceae.